2020
DOI: 10.1111/iej.13343
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory biomarkers in dentinal fluid as an approach to molecular diagnostics in pulpitis

Abstract: AimTo explore a set of inflammatory biomarkers obtained from dentinal fluid (DF) from patients with symptomatic irreversible pulpitis (IP), reversible pulpitis (RP) and normal pulp (NP).MethodologyA cross‐sectional exploratory study was performed, recruiting 64 patients on the basis of their respective pulp condition. DF samples were obtained from all patients (23, from IP patients; 20, from RP patients; and 21, from NP patients). Quantification of biomarkers was performed using a Luminex® MAGPIX platform syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 24 publications
2
38
0
Order By: Relevance
“…2011, Brizuela et al . 2020). The biochemical analysis of GCF or DF could be a useful non‐invasive diagnostic tool for decision making for management of a deep carious lesion.…”
Section: Discussionmentioning
confidence: 99%
“…2011, Brizuela et al . 2020). The biochemical analysis of GCF or DF could be a useful non‐invasive diagnostic tool for decision making for management of a deep carious lesion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dental fluid contained within dentinal tubules has been proposed to be potentially useful as a biomarker of different stages of pulpitis. By detecting the dental fluid in tooth cavities using polyvinylidene difluoride membrane, Brizuela et al [18] found that the biomarkers of fibroblast growth factors acid (FGF-acid), interleukin-1α (IL-1α), IL-6, and tissue inhibitor of metalloproteinases 1 (TIMP-1) may collectively be useful for molecular diagnostics in pulpitis. Due to its advantages of ease-of-use and non-invasiveness, the dental fluid test is a promising method for the molecular diagnosis of pulpitis.…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular or molecular level, a wide range of molecules are released during pulpal and periapical inflammation, including cytokines, proteases, inflammatory mediators, growth factors, and antimicrobial peptides [15,16]. Measurable levels of molecules can be found not only in pulp tissue but also in pulpal blood [17], dentinal fluid [18,19], periapical fluid [1], and gingival crevicular fluid [20], which can be collected noninvasively and analysed without extirpating the pulpal tissue [19,21,22]. The factors that can be used to assess the level of pulp inflammation are called biomarkers of pulpitis [23].…”
Section: Introductionmentioning
confidence: 99%
“…At the cellular or molecular level, a wide range of molecules are released during pulpal and periapical in ammation, including cytokines, proteases, in ammatory mediators, growth factors, and antimicrobial peptides [15,16]. Measurable levels of molecules can be found not only in pulp tissue but also in pulpal blood [17], dentinal uid [18,19], periapical uid [1], and gingival crevicular uid [20], which can be collected non-invasively and analysed without extirpating the pulpal tissue [19,21,22]. The factors that can used to assess the level of pulp in ammation are called biomarkers of pulpitis [23].…”
Section: Introductionmentioning
confidence: 99%